Aziridine carboxylate from D-glucose: synthesis of polyhydroxylated piperidine, pyrrolidine alkaloids and study of their glycosidase inhibition - Dhavale, Dilip D.; Kumar, K. S. A.; Chaudhari, Vinod D.; Sharma, T.; Sabharwal, Sushma G.; PrakashaReddy, J. (Organic & Biomolecular Chemistry, 2005)
The D-glucose derived aziridine carboxylate 5 was obtained from (E)-ethyl-6-bromo-1,2-O-isopropylidene-3-O-benzyl-5-deoxy-alpha-D-xylo-5 -eno-heptofuranuronate 4 through conjugate addition of benzylamine and in situ intramolecular nucleophilic expulsion of bromine. The regioselective aziridine ring-opening, using water as a nucleophile, resulted in the alpha-hydroxy-beta-aminoester 6, which was exploited in the synthesis of six and five membered azasugars 1b/1c and 2b/2c, respectively The glycosidase inhibitory activity of the title compounds was evaluated.

Alpha-geminal dihydroxymethyl piperidine and pyrrolidine iminosugars: synthesis, conformational analysis, glycosidase inhibitory activity, and molecular docking studies - Pawar, Nitin J.; Parihar, Vijay Singh; Chavan, Sanjay T.; Joshi, Rakesh S.; Joshi, Pranaya V.; Sabharwal, Sushma G.; Puranik, Vedavati G.; Dhavale, Dilip D. (Journal of Organic Chemistry, 2012)
The Jocic-Reeve and Corey-Link type reaction of dichloromethyllithium with suitably protected 5-keto-hexofuranoses followed by treatment with sodium azide and sodium borohydride reduction gave 5-azido-5-hydroxylmethyl substituted hexofuranoses 7a-c with required geminal dihydroxymethyl group. Removal of protecting groups and converting the C-1 anomeric carbon into free hemiacetal followed by intramolecular reductive aminocyclization with in situ generated C5-amino functionality afforded corresponding 5C-dihydroxymethyl piperidine iminosugars 2a-c. Alternatively, removal of protecting groups in 7b and 7c and chopping of C1-anomeric carbon gave C2-aldehyde that on intramolecular reductive aminocyclization with CS-amino gave 4C-dihydroxyrnethyl pyrrolidine iminosugars 1b and 1c, respectively. On the basis of the H-1 NMR studies, the conformations of 2a/2b were assigned as C-4(1) and that of 2c as C-1(4). The glycosidase inhibitory activities of all five iminosugars were studied with various glycosidase enzymes and compared with natural o-g/uco-l-deoxynojirimycin (DNJ). All the five compounds were found to be potent inhibitors of rice alpha-glucosidase with K-i and IC50 values in the nanomolar concentration range. Iminosugars 2b and 1b were found to be more potent inhibitors than their parent iminosugar. These results were substantiated by in silico molecular docking studies.